(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This study was carried out to evaluate examine the antimicrobial activity of some probiotics bacteria Filtrates upon aerobic and anaerobic bacteria that consisting of gingivitis infections and accumulation of bacterial plaque. So the living cells of four probiotics bacteria cultures were prepared that developing in the skim milk 12%, the probiotics bacteria were Lactobacillus rhamnosus GG, Lactobacillus plantarum , Lactobacillus reuteri and Bifidus actiregularis (Bifidus regularis), the probiotics bacteria were counted and it reached > 108, culture cells filtrate was prepared and both aerobic and anaerobic bacterial plaque were isolated and tested the ability of inhibition of culture cells filtrate , the results showed that the culture cells filtrate of Lactobacillus rhamnosus GG bacteria the best inhibition where was 2.57 logarithmic cycle for aerobic bacteria and 2.28 logarithmic cycle for anaerobic bacteria. Three groups of volunteers divided into 12 volunteers for each group to compare the effectiveness of that Lactobacillus rhamnosus GG bacteria culture filtrate with chlorhexidine mouthwash and placebo, volunteers were subjected to the experiment for 14 days under medical supervision, the results showed the efficiency of the Lactobacillus rhamnosus GG culture filtrate mouthwash and chlorhexidine in reducing the accumulation of the lamina bacterial plaque compared to placebo, the Lactobacillus rhamnosus GG culture filtrate showed efficiency according to the standard germ guide plate (Plaque index) and the standard gingivitis guide plate (gingival index).